Unimed Students' Views on Political Dynamics in the 2024 Presidential Election - Simanjuntak, Putri Lorenza; Simarmata, Diva Nancy Audissa; Lubis, Nasya Adinda Putri; Sembiring, Marselinus Eprimsa (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
Empowering students is a promising method for increasing people's participation in elections. Even though the number of students who vote may not be significant, what is important is that they spread political literacy through their intelligence and academic quality. Students must be involved in various activities to increase political understanding, awareness and involvement, especially those related to the electoral process. Because there are no contemporary national leaders who can serve as good examples, according to Tjetje H. Padmadinata (Citizenship Political Education Surgery, 2016). Currently, it is very important for students to be involved in increasing political awareness through political education. This is due to the fact that the political branding received by society tends to be negative, influenced by unpleasant political experiences and the lack of examples of good national leaders. The leadership crisis that is currently occurring in Indonesia